Error Bound for Bernstein-Bézier Triangular Approximation (Journal of Computational Mathematics, 2021)
Based upon a new error bound for the linear interpolant to a function defined on a triangle and having continuous partial derivatives of second order, the related error bound for n-th Bernstein triangular approximation is obtained. The order of approximation is 1/n.